Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/1365-2435.13570
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific trait integration increases with environmental harshness: A case study along a metal toxicity gradient

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…The reason underlying this difference might be that the driver of trait variation within a species was different from that within a plot: Environment and seedling size influenced intraspecific trait variation while species identity and seedling size were the causes of trait variation within a plot. This environment‐driven trait variation within a species might increase constraints of trait combinations, thus a stronger correlation than that within a plot (Table 1) (Delhaye et al., 2020; Dwyer & Laughlin, 2017). Finally, our results indicated that trait variance and sample size together explained a large amount of variation (39%–89%, Table 1) in the strength of trait correlations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason underlying this difference might be that the driver of trait variation within a species was different from that within a plot: Environment and seedling size influenced intraspecific trait variation while species identity and seedling size were the causes of trait variation within a plot. This environment‐driven trait variation within a species might increase constraints of trait combinations, thus a stronger correlation than that within a plot (Table 1) (Delhaye et al., 2020; Dwyer & Laughlin, 2017). Finally, our results indicated that trait variance and sample size together explained a large amount of variation (39%–89%, Table 1) in the strength of trait correlations.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent broad‐scale studies find that leaf size is decoupled with economics traits (Diaz et al., 2016; Thomas et al., 2020). The correlations (or conversely, independence) between these leaf traits are important for plants and their ability to adapt to environmental gradients (Delhaye et al., 2020; Dwyer & Laughlin, 2017; Li et al., 2015). Studies that examine leaf economics usually measure leaf traits from the lamina only, but a whole leaf includes both lamina and petiole.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our previous phenotypic selection analysis showed that increased density also led to reduced fitness [24]. An increase in trait integration with soil metal toxicity was also found in 65 representative species of copper flora from the Katangan Copperbelt [39]. The opposite was found for Arabidopsis thaliana in competition with Lolium multiflorum [40].…”
Section: Discussionmentioning
confidence: 85%
“…However, it did not reflect advantages for survival or growth, since Cytharexylum had the lowest δ 13 C values and was the species with the highest survival rate. The δ 13 C has been used to evaluate the acclimation to irradiance as a time-integrated response of photosynthesis in field conditions (Zimmerman and Ehleringer 1990, Dawson et al 2002). However, differently from photochemical evaluations, the irradiance treatments did not promote significant changes in the δ 13 C values, except for Cytharexylum.…”
Section: Discussionmentioning
confidence: 99%
“…Plant performance in stressful environments depends on both individual and coordinated adjustments in functional traits (Bongers et al 2017, Delhaye et al 2020. For example, high irradiance can improve the carbon gain and favor the plant growth, but it comes at the cost of adjusting several, if not all, leaf traits to avoid photoinhibition (Vieira et al 2015).…”
Section: Introductionmentioning
confidence: 99%